Tailored Predictive Indicators for Weaning Success from High-Flow Nasal Cannula in Postoperative Hypoxemic Patients - Yuh-Chyn Tsai; Shih-Feng Liu; Hui-Chuan Chang; Ching-Min Huang; Wan-Chun Hsieh; Chin-Ling Li; Ting-Lung Lin; Ho-Chang Kuo (Life)
The use of high-flow nasal cannula (HFNC) as an oxygen therapy post-extubation has demonstrated varying success rates across different surgical populations. This study aimed to identify the predictive factors influencing HFNC weaning outcomes in patients with postoperative extubation hypoxemia. We conducted a retrospective analysis of patients in a surgical intensive care unit, categorized into three major postoperative groups: cardiothoracic surgery, upper abdominal surgery, and other surgeries. Our analysis examined pre-extubation weaning profiles, vital signs before and after HFNC initiation, and changes in physiological parameters during HFNC use. A total of 90 patients were included, divided into two groups based on HFNC weaning success or failure. Key parameters analyzed included maximal inspiratory pressure (MIP), PaO2/FiO2 (P/F) ratio, vital signs, SpO2 levels, respiratory rate (RR), heart rate (HR), respiratory rate–oxygenation (ROX) index, and HFNC duration. The findings revealed that cardiothoracic and upper abdominal groups showed significantly higher HFNC weaning success rates (73.3% and 70.6%) compared to the other surgeries group (34.6%) (p = 0.004). Critical predictors of successful weaning included pre-HFNC SpO2, P/F ratio, and changes in the ROX index, particularly in upper abdominal and other surgeries groups. In cardiothoracic surgery patients, higher maximal inspiratory pressure (MIP) (p = 0.031) was associated with improved outcomes, while prolonged HFNC use correlated with weaning success in this group (p = 0.047). These findings underscore the necessity of tailoring HFNC strategies to surgical characteristics and individual patient profiles. For cardiothoracic surgery patients, pre-extubation MIP, post-extubation RR, ΔROX, and ΔHR were identified as key predictive factors. In upper abdominal surgery, pre-extubation P/F ratio, post-extubation SpO2, and ΔROX played crucial roles. For patients undergoing other types of surgeries, pre-extubation P/F ratio and ΔROX remained the most reliable predictors of HFNC weaning success.